Особенности биоклиматических условий Приволжского федерального округа - Исаева (Isaeva Marina), Марина Валерьевна; Переведенцев (Perevedentsev Yuri), Юрий Петрович (Географический вестник=Geographical bulletin, 2017)
На основе комплексного учета метеорологических величин дается оценка ряда биоклиматических характеристик Приволжского округа с целью выявления комфортных и дискомфортных условий проживания человека. К л ю ч е в ы е с л о в а: прикладная климатология; биоклимат; биоклиматические индексы; комфортные условия. BIOCLIMAT CONDITIONS FEATURES OF PRIVOLZHSKY FEDERAL REGION Results of calculations of seasonal and annual spatial distribution of bioclimatic indexes with an estimation of comfort of territory. Laws are revealed and schemes of their spatial distribution have been constructed. It is established that distribution of the basic bioclimatic indexes at Privolzhsky region arotidsи by rather big spatial heterogeneity and time variability during the various periods of year. Time tendencies of all considered indicators testify to improvement of bioclimatic conditions during the cold period of year in Privolzhsky region and stability in the warm. K e y w o r d s: applied climatology; bioclimatic; bioclimatic indexes; comfort conditions.